Analysis of the emotional communication of brands through the anthropomorphization of virtual influencers: Case Lil Miquela - Castañeda, Stefanny (2024)
There is a tendency for many brands to incorporate themselves into the lifestyle of influencers. However, one type of influencers that is standing out are the virtual ones, who have managed to empathize with the public and anthropomorphize their image with the brands they sponsor. This research aims to know how brands connect emotionally with their audience through the anthropomorphization of virtual influencers. Being the case study, the virtual influencer Lil Miquela. For this, a qualitative methodology was used through in-depth interviews with followers of this influencer. The main findings show that the virtual influencer generates interest in following her, as well as in wanting to have a life similar to hers in conjunction with the products and brands she uses. In that sense, brands could bet on incorporating virtual influencers as a tool within their advertising campaigns.